2014
DOI: 10.1074/jbc.m114.576975
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Derivatives as Bitter Taste Receptor (T2R) Blockers

Abstract: Background: T2Rs are activated by hundreds of bitter compounds; however, only five blockers are known. Results: T2R4 residues involved in binding to agonist quinine and two novel bitter blockers GABA and BCML were identified. Conclusion: Bitter blockers and agonists share the same orthosteric site in T2R4. Significance: Bitter blockers identified in this study have tremendous physiological and nutraceutical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 40 publications
8
99
0
Order By: Relevance
“…23,24) Inhibition of hTAS2Rs, especially hTAS2R14, would be one approach to reducing the bitterness of drugs. To date, only a few bitter inhibitors have been discovered that block bittersubstance-evoked hTAS2R activation, such as Sakuranetin for hTAS2R31, 25,26) 6-methoxyflavanones for hTAS2R39, 27,28) γ-aminobutyric acid (GABA), N α ,N α -bis(carboxymethyl)-L-lysine (BCML) 29) and abscisic acid 30) for hTAS2R4, and (R)-Citronellal for hTAS2R43 and hTAS2R46. 31) Batenburg et al identified several hTAS2R14 receptor antagonists from a screening of synthetic compounds; however, the nature of these compounds did not allow their effects to be validated in vivo before extensive safety evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…23,24) Inhibition of hTAS2Rs, especially hTAS2R14, would be one approach to reducing the bitterness of drugs. To date, only a few bitter inhibitors have been discovered that block bittersubstance-evoked hTAS2R activation, such as Sakuranetin for hTAS2R31, 25,26) 6-methoxyflavanones for hTAS2R39, 27,28) γ-aminobutyric acid (GABA), N α ,N α -bis(carboxymethyl)-L-lysine (BCML) 29) and abscisic acid 30) for hTAS2R4, and (R)-Citronellal for hTAS2R43 and hTAS2R46. 31) Batenburg et al identified several hTAS2R14 receptor antagonists from a screening of synthetic compounds; however, the nature of these compounds did not allow their effects to be validated in vivo before extensive safety evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The mutants were synthesized commercially (Genscript USA Inc, NJ, USA). All the genes were cloned into pcDNA3.1 and transiently co-expressed in HEK293T cells with the chimeric G-protein Gα16/44 using lipofectamine-2000, as described previously (11,29). Cells were propagated in DMEM-F12 media, at 37 °C under 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were propagated in DMEM-F12 media, at 37 °C under 5 % CO 2 . Flow cytometry studies for elucidating cell surface expression of the receptors were carried out using the anti-FLAG antibody, exactly as described recently (11) . Intracellular calcium mobilization assays.…”
Section: Methodsmentioning
confidence: 99%
“…Other compounds (such as the endogenous γ-aminobutyric acid or Nα,Nα-bis(carboxymethyl)-L-lysine) are reportedly T2R4 antagonists, with IC 50 s of 3.2 µM and 59 nM respectively; Nα,Nα-bis(carboxymethyl)-L-lysine acts rather as an inverse agonist (Pydi, Sobotkiewicz, et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%